Quality of life before and after total laryngectomy: Results of a multicenter prospective cohort study. Issue 3 (1st June 2013) - Singer, Susanne; Danker, Helge; Guntinas–Lichius, Orlando; Oeken, Jens; Pabst, Friedemann; Schock, Juliane; Vogel, Hans‐Joachim; Meister, Eberhard F.; Wulke, Cornelia; Dietz, Andreas
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to determine what quality of life (QOL) areas improve and deteriorate during the first year after total laryngectomy and to identify predictors of these changes. Methods One hundred seventy‐four patients completed the European Organization for Research and Treatment of Cancer (EORTC) QOL questionnaires before laryngectomy, n = 133 before discharge from hospital, n = 110 at the end of rehabilitation, and n = 86 1 year after laryngectomy. Multivariate regression analysis was performed to estimate the effect of potential predictors on QOL. Results Areas that did not recover to baseline level were physical functioning, role functioning, social functioning, fatigue, dyspnea, appetite loss, financial difficulties, senses, speech, and social contact, whereas global health status, coughing, and weight improved. There was no evidence for predicting effects of age, sex, education, and tumor site. Tumor stage, recurrent disease, radiotherapy, and mental health did display predicting effects. Smoking status before the treatment had marginally significant effects. Conclusion QOL decreases initially after laryngectomy; some QOL areas recover slowly over the course of the year after surgery, and some remain significantly worse than at baseline. © 2013 Wiley Periodicals, Inc. Head Neck36: 359–368, 2014